Pengaruh Program Pelatihan Pengolahan Sampah Padat Organik Menggunakan Metode Composting Terhadap Pengetahuan Dan Ketrampilan Ibu-Ibu PKK Di RW III Kelurahan Boja Kabupaten Kendal - Salawati, Trixie; Astuti, Rahayu; Hayati, Rizki Nurul (Jurnal Promosi Kesehatan Indonesia, 2008)
Background: Garbage is discard materials as a result of human life. The amount of garbage yielded by human being is increased progressively that require to be handled to prevent from one way to handled garbage especially organic garbage is by processing them to become compost.. Composting is process decomposition of garbage biologically either in aerobic or anaerobic condition. Many people do not understand how to process solid waste becomes compost. This study aims to know the effects of training in composting garbage at PKK’s member at Kendal District.Method: The study is action research using Pre Test Post Test Design. 30 women were selected purposively using certain criteria. The data analyzed using Paired t-test and Wilcoxon test to compare the result before and after training.Result: The study shows that there were significant differences between level of knowledge of women before and after training. However the significant differences between before and after training in terms of the level of knowledge and attitudes 1 month after training whereasthe skills after training increase significantly.Keywords: training, knowledge, skilled, composting, garbage